2014
DOI: 10.1371/journal.pone.0111255
|View full text |Cite
|
Sign up to set email alerts
|

CARD14 Expression in Dermal Endothelial Cells in Psoriasis

Abstract: Mutations in the caspase recruitment domain, family member 14 (CARD14) gene have recently been described in psoriasis patients, and explain the psoriasis susceptibility locus 2 (PSORS2). CARD14 is a scaffolding protein that regulates NF-κB activation, and psoriasis-associated CARD14 mutations lead to enhanced NF-κB signaling. CARD14 is expressed mainly in epidermal keratinocytes, but also in unidentified dermal cells. In this manuscript, the identity of the dermal cell types expressing CARD14, as well the pote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
52
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(53 citation statements)
references
References 33 publications
0
52
0
1
Order By: Relevance
“…Harden et al (2014) also showed that CARD14 expressed in dermal endothelial cells could modulate the expression of chemokines such as CXCL8, CXCL10, and CCL2, which sensitize the skin vasculature of psoriasis patients bearing CARD14 mutations to inflammation. Because psoriasis is often associated with cardiovascular comorbidities, these observations might also imply a role for CARD14 in cardiovascular disease (Yim and Armstrong, 2016).…”
mentioning
confidence: 93%
“…Harden et al (2014) also showed that CARD14 expressed in dermal endothelial cells could modulate the expression of chemokines such as CXCL8, CXCL10, and CCL2, which sensitize the skin vasculature of psoriasis patients bearing CARD14 mutations to inflammation. Because psoriasis is often associated with cardiovascular comorbidities, these observations might also imply a role for CARD14 in cardiovascular disease (Yim and Armstrong, 2016).…”
mentioning
confidence: 93%
“…Conversely, CARD14 mRNA is virtually undetectable in T-lymphocytes and monocytes, suggesting that the gene is specifically required for the maintenance of skin immune homeostasis (Fuchs-Telem et al, 2012;Harden et al, 2014). In keeping with this notion, gain-of-function CARD14 mutations have been linked to a number of inflammatory dermatoses.…”
Section: Introductionmentioning
confidence: 89%
“…The gene is most prominently expressed in skin, as transcript levels are high in keratinocytes and moderately abundant in dermal endothelial cells (Fuchs-Telem et al, 2012;Harden et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…A CARD-14 protein többek között felelős az NFκB aktivitásának regulációjáért, így közvetett markere lehet az NFκB aktivitásának. A psoriasisos beteg endothelsejtjein kimutatott CARD-14-pozitivitás összefüggésben lehet a szisztémás gyulladás kialakulásával, továbbá a cardiovascularis komorbiditások megjelenésével [8].…”
Section: A Psoriasis Patofiziológiájaunclassified